Prevalence of Antibiotic Purchase Online and Associated Factors Among Chinese Residents: A Nationwide Community Survey of 2019 - Sun, Na; Gong, Yanhong; Liu, Jiaming; Wu, Jianxiong; An, Rongrong; Dong, Yue; Zhu, Yi; Mu, Ketao; Zhang, Guopeng; Yin, Xiaoxv (Frontiers in Pharmacology, 2021)
Introduction: Online sales of antibiotics have increased public access to these medicines. This study aimed to analyze the online antibiotic purchase behavior of the Chinese residents and identify its associated factors. Methods: We conducted a nationwide cross-sectional online survey among Chinese community residents from January 20 to February 28, 2019. A structured questionnaire was used to collect data on their sociodemographic characteristics, health-related variables, and the online antibiotic purchase behavior in the past three months. Descriptive statistics and logistic regression analyses were used. The statistical analyses were performed using SAS version 9.4 (SAS Institute Inc). Results: A total of 101,120 respondents were included in the analysis. The weighted prevalence of antibiotic purchase online was 3.71% (95% CI, 3.53%-3.88%). Residents who purchased antibiotics online were more likely to be older (age≥65 years), be a male, live in rural areas, have a higher education level, report an excellent economic status, suffer from chronic diseases, and search for health information on the internet. Conclusion: Numerous residents had purchased antibiotics online in the past three months throughout China. We should pay more attention to this behavior. There is a need to strengthen regulation of antibiotic sales online and improve public education on antibiotic purchase online. More comprehensive information on antibiotic purchase online as well as the advantages and disadvantages of online sales of antibiotics should be investigated in the future studies.